By the Governor. 1878. Thanksgiving proclamation, Territory of Idaho : the President has set apart Thursday, the twenty-eighth day of November, instant, as a day of Thanksgiving ... it is recommended to the good people of Idaho that they suspend their accustomed employments, and devote the day to solemn and grateful religious services ... Done at Boise City, this fifth day of November, A.D. 1878. M. Brayman, Governor, attest, R.A. Sidebotham, secretary ([publisher not identified], 1878)
November 5, 1878 Governor M. Brayman's proclamation setting November 28th as a day of Thanksgiving, for the temporal and spiritual blessings from God.